Expression of miRNAs in turkey muscle satellite cells and differential response to thermal challenge - Reed, Kent M.; Mendoza, Kristelle M.; Kono, Thomas; Powell, Ashley A.; Strasburg, Gale M.; Velleman, Sandra G. (Frontiers in Physiology, 2023)
Thermal stress alters the transcriptome and subsequent tissue physiology of poultry; thus it can negatively impact poultry production through reduced meat quality, egg production, health and wellbeing. Modulation of gene expression is critical to embryonic development and cell proliferation, and growing evidence suggests a role for non-coding RNAs (RNA:RNA interaction) in response to thermal stress in animals. MicroRNAs (miRNAs) comprise a class of small regulatory RNAs that modulate gene expression through post-transcriptional interaction with and regulation of mRNAs, potentially altering numerous cellular processes. This study was designed to identify and characterize the differential expression of miRNAs in satellite cells (SCs) from the turkey pectoralis major muscle, and to predict important miRNA:mRNA interactions in these developing SCs under thermal challenge. Small RNA sequencing was performed on RNA libraries prepared from SCs cultured from 1-week-old male Nicholas Commercial turkeys (NCT) and the non-selected Randombred Control Line 2 (RBC2) turkeys during proliferation and differentiation at control temperature (38°C) or under thermal challenge (33°C or 43°C). A total of 353 miRNAs (161 known and 192 novel) was detected across the sequenced libraries. Expression analysis found fewer differentially expressed miRNAs in SCs of NCT birds suggesting that miRNA response to heat stress has been altered in birds selected for modern commercial growth traits. Differentially expressed miRNAs, including those with described roles in muscle development, were detected both among temperature treatments and between genetic lines. Prominent differential expression of miR-206 was found in proliferating turkey SCs with a significant response to thermal challenge in both lines. In differentiating SCs, isoforms of miR-1 had significant differential responses with expression of miR-206 being mainly affected only by cold treatment. Target gene predictions and gene ontology analysis suggests that differential expression of miRNAs during thermal stress could significantly affect cellular proliferation and differentiation.